Nutritional and Quality Assessment of some Irrigated Wheat Genotypes in Nigeria - Abubakar, F.; Zigla, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
The aim of this study is to evaluate the nutritional and end-use qualities of some advanced irrigated Nigerian grown wheat genotypes which was developed and produced by Lake Chad Research Institute, Maiduguri, Borno State of Nigeria. Standard methods were used to determine the physical, milling, proximate, baking, sensory, functional, rheological and textural qualities of the Nigerian grown wheat. The result showed that grain physical characteristics of the eleven irrigated wheat genotypes were statistically significant. Flour extraction differed significantly from 66.1-79.6% in the irrigated wheat genotypes. Three irrigated genotypes namely, Florkwa-2, Soonot 5, and Hubara-3 had the highest flour extraction rate with flour yield above 75%. Proximate flour quality indicated significantly higher protein content in Hubara (15.2%), Pastor-2 (15.8%), Kauz (16.2%), Soonot-5 (15.8%), while Katila-17 had higher carbohydrate (73.2 %) than Hubara-1. The results for dough and bread functional and textural qualities further showed that Attila-7, Katilla17, Angi-2 and Soonot-5 were superior to the other genotypes, and comparable to the standard imported flour. However, bread sensory evaluation gave the standard flour higher score rating. Therefore, the nutritional and end use quality indicated that Nigerian grown wheat had properties suitable for bread production. The wheat genotypes namely Soonot -5 and Attila-7, among the other irrigated genotypes used in this study, were rated higher in bread baking quality and were even comparable to the standard imported flour which indicated that Nigerian grown wheat can be used to produce bread